E.L.E.T.T.R.A. - López, Temístocles, 1947-; Starr, Ben (Producer); Marconi, Elettra (KayStarr : Radio Australasia, 2015)
A story about the extraordinary life and inventions of Guglielmo Marconi, the father of wireless communication.